Analysis Of Competency Test Problems In Class Viii Mathematics Books With Basic Competencies - Yogi Prayulia Trisandi; Maimunah Maimunah; Yenita Roza (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
The purpose of this study is to describe the cognitive level of the questions in the eighth grade mathematics textbook on the material of the Pythagorean theorem, circles and tangents to circles according to the revised bloom taxonomy. In this study, the research subject was a competency test item contained in the Mathematics book for SMP / Mts Class VIII Semester 2 written by M Cholik Adinawan and published by Erlangga as many as 101 questions divided into 33 questions of competency 1, competency test 2 of 39 and competency test 3 as many as 29 questions. This research was conducted by analyzing the cognitive level of the questions based on the cognitive process in solving the questions. Based on the cognitive indicators of the revised bloom taxonomy, each cognitive level of questions was classified into six cognitive levels. The result of this research is the cognitive level in each competency test. The results of each cognitive level of the material pythagorean theorem C1 3.03%, C2 6.06%, C3 60.6%, C4 24.24%, C5 6.06%, and C6 0%. The results of the cognitive process level questions on the subject circle C1 2.56%, C2 25.64%, C3 51.28%, C4 20.51%, C5 and C6 0%. And the results of the cognitive process level questions on the subject tangent to circle C2 21.42%, C3 62.06%, C4 17.24% and C1, C5 and C6 0%. These results meet the achievement criteria for Basic Competence at C3 and C4 as much as 40%, do not meet the achievement for C1 and C2 as much as 30% and C5 and C6 as much as 30%. From the above results it can be concluded that the percentage of question analysis has not fulfilled the distribution of questions that support the achievement of basic competencies